Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/1521-4141(200208)32:8<2282::aid-immu2282>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II isotype-specific signaling complex on human B cells

Abstract: The highly polymorphic human major histocompatibility complex (HLA) class II molecules are acknowledged as signaling receptors although their coupling to signaling pathways is not yet fully elucidated. In this study, we investigated how HLA class II can be coupled to protein tyrosine kinase (PTK) signaling pathway in B cells and whether there might be differences depending on HLA class II isotype. Using the human B cell line Ramos, we demonstrate that CD19 and CD20 are two HLA class II‐associated receptors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…23 These proteins are also important receptors that have been shown to participate in transmembrane and cytoplasmic signaling. [24][25][26] Although upregulated on the surface membrane of human malignant B-cells, HLA proteins are even more abundant inside these cells (Fig. 8), where they are manufactured and assembled on the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…23 These proteins are also important receptors that have been shown to participate in transmembrane and cytoplasmic signaling. [24][25][26] Although upregulated on the surface membrane of human malignant B-cells, HLA proteins are even more abundant inside these cells (Fig. 8), where they are manufactured and assembled on the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, relevant microdomains containing peptide-MHC have been shown to interact with CD82 and other members of the tetraspan family of integral membrane proteins (38). CII has also been shown to associate with CD19 and CD20, molecules that may couple CII to the protein tyrosine kinase signaling pathway (21). Other molecules have also been reported to be associated with CII, including CD40 (39).…”
Section: Discussionmentioning
confidence: 99%
“…The different results in our study from those reported before may be due to the binding properties of the different Abs or the type of CII. Indeed, in the mouse study (2), the rate of cell death was related to the type of the Ab used, and different classes of HLA have been found to signal differently following their ligation with anti-HLA Abs (21). Furthermore, in the former study, staining with ethidium bromide has been taken as evidence for B cells undergoing apoptosis in the absence of data showing specific DNA fragmentation.…”
Section: Differential Effect Of Ab Ligation Of Type I and Ii Complexementioning
confidence: 99%
“…These include B cell activation status (15,16), species differences (8,15), B cell transformation (8), MHC II haplotype or isotype (4,9,17), and signals generated from other cell surface receptors, including the BCR (18) or CD40 (19). Additionally, other factors such as the uptake and processing of Ag may influence the context in which MHC II is found in the plasma membrane and, as a result, dictates the functional outcome of MHC II-mediated signals in B cells.…”
Section: Dynamics Of Mhc Class Ii-activating Signals In Murinementioning
confidence: 99%